Science and Technology for Community: Improving Web Programming Skills using Laravel Framework - Agus Eko Minarno; Lailis Syafa'ah; Dwi Rahayu (Direktorat Penelitian dan Pengabdian Kepada Masyarakat, 2021)
The essence of technology is to help human work become easier, cost effective, save time more efficiently and on target. The use of technology that is studded with innovation provides real changes in every activity, including in the world of education. Even in some countries such as Australia and Hong Kong, technology has been introduced through basic programming since the age of 3 years. In Indonesia in 2016 the Minister of Communication and Information, Rudiantara, has discussed programming so that it is included in the elementary school curriculum. The introduction of technology at the elementary school level aims to prepare young people who are ready to face technology in the industrial era 4.0. This service activity is carried out in order to improve web programming capabilities using the Laravel framework. The hope is that by providing the ability to program using the Laravel framework, it can support academic education and increase employment opportunities with more capabilities.